PENGARUH PEMBERIAN SEDIAAN TOPIKAL EKSTRAK BAWANG MERAH (Allium cepa L.) TERHADAP PENYEMBUHAN LUKA SAYAT PADA TIKUS (Rattus norvegicus) - Deinike Wanita Marwan; Wahyu Ramadhan; Elly Anggreny (Collaborative Medical Journal, 2023)
According to Riskesdas in 2013 the prevalence of wounds in Indonesia was 8.2%. Types of injuries that are mostly experienced by the population are cuts / cuts (23.2%). Shallots have various properties, one of which is to repair tissue. One of the ingredients in red onion is in the form of flavonoids which are used as anti- inflammatory, antibacterial, and antioxidant properties. This study aims to determine the effect of topical application of shallot extract (Allium cepa L.) on wound healing in male rats (Rattus norvegicus). This research is an experimental study with a post-test only research design with a control group design. The rats were divided into 5 groups randomly. Each group consisted of 6 rats including the negative control group, the positive group was given bioplacenton, 3 treatment groups were given 30%, 60%, 90% topical preparation of shallot extract, respectively. Data analysis was performed using the One Way Anova test and Post Hoc Bonferroni tests were carried out.concentration of 30%, 60%, and 90% have an effect on wound healing, the highest concentration is at a concentration of 90%. The lowest concentration is at 30%.